Divergence in red light responses associated with thermal reversion of phytochrome B between high‐ and low‐latitude species. Issue 1 (4th May 2021) - Ikeda, Hajime; Suzuki, Tomomi; Oka, Yoshito; Gustafsson, A. Lovisa S.; Brochmann, Christian; Mochizuki, Nobuyoshi; Nagatani, Akira
Summary: Phytochromes play a central role in mediating adaptive responses to light and temperature throughout plant life cycles. Despite evidence for adaptive importance of natural variation in phytochromes, little information is known about molecular mechanisms that modulate physiological responses of phytochromes in nature. We show evolutionary divergence in physiological responses relevant to thermal stability of a physiologically active form of phytochrome (Pfr) between two sister species of Brassicaceae growing at different latitudes. The higher latitude species ( Cardamine bellidifolia ; Cb ) responded more strongly to light‐limited conditions compared with its lower latitude sister ( C. nipponica ; Cn ). Moreover, CbPHYB conferred stronger responses to both light‐limited and warm conditions in the phyB ‐deficient mutant of Arabidopsis thaliana than CnPHYB : that is Pfr CbphyB was more stable in nuclei than CnphyB. Our findings suggest that fine tuning Pfr stability is a fundamental mechanism for plants to optimise phytochrome‐related traits in their evolution and adapt to spatially varying environments, and open a new avenue to understand molecular mechanisms that fine tune phytochrome responses in nature.